Talulah's back in town - Novak, Brenda (Novak, Brenda. Coyote Canyon novel., 2023)
Returning home to Coyote to sell her late aunt's home, Talulah Barclay, in this place where no one has forgiven her for leaving her fiancé at the altar, discovers she still has close friends who rally around her when someone sets out to make sure she's not welcome in town.